Earth system responses to different levels of greenhouse gas emissions mitigation - Friedlingstein, Pierre; Artaxo, Paulo; Gallego-Sala, Angela V.; Jia, Gensuo; Jones, Chris D.; Kawamiya, Michio; Loisel, Julie; Loutre, Marie-France; Rehfeld, Kira; Rovere, Alessio; Smith, Chris; Séférian, Roland; et al. (Frontiers in Climate, 2024)
Anthropogenic carbon dioxide (CO2) emissions are the main driver of climate change, with global warming increasing almost linearly with cumulative CO2 emissions. Hence, future warming will primarily result from future emissions of CO2 with contributions from other greenhouse gases (mostly CH4 and N2O) and aerosols. Climate projections of the 21st century, such as those assessed by the IPCC, are provided from comprehensive climate models, also called Earth System models, driven by scenarios of the 21st century evolution of emissions from those climate forcers. While it seems now inevitable that the world will reach 1.5°C of warming above pre-industrial levels by the early 2030s, the extent to which we exceed this warming level and how quickly we may be able to reduce temperatures again depends strongly on global activity taken now to limit emissions. In this paper, we review the current understanding on Earth system changes under two highly contrasted possible future worlds. We first focus on high-end scenarios, where anthropogenic emissions continue to increase over the course of the 21st century, leading to large warming levels, associated impacts on all components of the Earth System, and increased risks of triggering tipping points. We then assess low-end scenarios, where anthropogenic emissions rapidly decline, reaching net zero and potentially becoming net negative before the end of the 21st century. Such “overshoot” scenarios lead to a peak in global warming followed by a slow decline in global temperature, with some degree of reversibility in the global carbon cycle and key Earth system components. We also review paleoclimatic information relevant to these two contrasting future worlds. Paleoclimate evidence for geo-biosphere interactions shows that stabilizing feedbacks operate on millennial or longer timescales, whereas destabilizing feedbacks and tipping cascades occurred also on shorter timescales.